External Whistleblowing Intentions in Accounting Students: An Overview based on Relativism and Gender - Martadinata, I Putu Hendra; Pasek, Nyoman Suadnyana; Wahyuni, Made Arie (Universitas Pendidikan Ganesha, 2023)
This study aims to examine the effect of relativism and gender on external whistleblowing intentions of accounting students. This study uses a quantitative design through a survey approach, with a sample of 112 undergraduate accounting students. The results of this study found that relativism has a positive influence on students' external whistleblowing intentions. For the gender variable, this study did not find a significant difference in intentions between male and female students. Furthermore, this study found no effect of gender in moderating the relationship between relativism and students' external whistleblowing intentions. The results of this study are expected to contribute theoretically through a more proactive approach in explaining the intention to report fraud, especially at the student level. Practically, the results of this study are expected to be used as consideration for organizations in providing more effective reporting channels to resolve internal problems.